2016
DOI: 10.1016/j.jvs.2015.10.061
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of open total arch replacement in the modern era

Abstract: The main findings from this meta-analysis indicate that total aortic arch replacement can be performed with satisfactory mortality and morbidity. The pooled rates of mortality and permanent neurologic deficit among elective cases were surprisingly low, and these data have an even greater prominence when they are compared with outcomes of hybrid arch series. Under urgent/emergency surgery, early mortality and neurologic complications showed an about threefold higher rate. Moderate hypothermic circulatory arrest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 41 publications
(164 reference statements)
7
54
0
3
Order By: Relevance
“…Modern advancements in open surgical techniques have contributed to better outcomes and lower complication rates for thoracic aortic replacement surgery . The overall decreases in mortality rates have also coincided with the implementation of HCA brain protection techniques, which are now an essential part of thoracic aortic replacement surgery .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Modern advancements in open surgical techniques have contributed to better outcomes and lower complication rates for thoracic aortic replacement surgery . The overall decreases in mortality rates have also coincided with the implementation of HCA brain protection techniques, which are now an essential part of thoracic aortic replacement surgery .…”
Section: Discussionmentioning
confidence: 99%
“…However, our reported rate is in line with more current literature. Settepani et al in a review of 21 studies of patients who underwent open thoracic aortic arch surgery, found that the pooled postoperative permanent and transient neurologic deficit rate were 3.4% and 5.2%, and in elective patients 2.9% and 2.2%, respectively. Similar low rates have been reported in other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Replacement of the aortic arch with a Dacron® prosthesis may be future‐proofed for subsequent disease progression or the need for staged treatment by leaving an elephant trunk (everted length of tube graft) or frozen elephant trunk (attached stent‐graft deployed antegradely) in the descending thoracic aorta to provide a suitable proximal landing zone for subsequent thoracic endovascular repair (TEVAR). A recent meta‐analysis of 21 studies, comprising some 2880 patients undergoing open arch repair, gave pooled elective operative mortality and permanent neurological deficit rates of 2·9 and 2·2 per cent respectively. There was a threefold increase in these rates in patients requiring urgent or emergency surgery.…”
Section: Indications For Aortic Arch Repairmentioning
confidence: 99%
“…Open repair is the reference standard, but requires cardiopulmonary bypass and hypothermic circulatory arrest and is associated with mortality and an incidence of cardiac and cerebrovascular events. The contemporary results of these procedures have been detailed in a recent meta‐analysis, which reported rates of operative mortality of 5·3 per cent, permanent stroke 3·4 per cent, permanent spinal cord injury 0·6 per cent and renal failure 4·1 per cent. The literature also demonstrates that the mortality and morbidity associated with these procedures increases markedly when significant co‐morbid factors are present, and these risks can preclude surgery.…”
Section: Introductionmentioning
confidence: 99%